Mechanical and electrical fields of piezoelectric curved sensors - Arslan, E.; Usta, R. (Archives of Mechanics, 2014)
Based on the theory of elasticity, a comprehensive mathematical model is developed for a piezoelectric bimorph curved bar which is in a closed electrical circuit. First, the model is verified by considering an actuator under an initial electric potential, and the numerical results are compared with those of a related study in the literature. Then, the model is used to obtain the mechanical and electrical fields of a bimorph curved sensor subjected to a couple at its free end section. Hence, the bending that causes the generation of electric potential in the sensor is investigated. The influence of the applied couple on the mechanical and electrical fields in the curved sensor is examined, and the results are presented in graphical form.